Shifting meanings, forgotten meanings: metaphor as a force for language change - Holmquist, Kelly (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
All living languages are in a aconstant state of evolution. Metaphorical usage is an important driving factor in that process of evolution; the blending of concepts within metaphor leads to the diversification of the reference of words used metaphorically. It can occur that a metaphorical usage becomes conventionalized. This, in turn, leads dto shiftis in the meanings of those words. Metaphorical usage can occur in a variety of forms, including metonymy, synecdoche, and euphemism. The effects of metsphoricalusage-and the closely related figure, simile-can even be seen in the evolution of the grammatical structures of many languages. I present various examples which demonstrate the role of metaphorical usage in the evolution of word-meanings and grammatical structures from PIE to modern Indo-European languages.